Education, Growth and Income Inequality - Coen N. Teulings; Thijs van Rens (Tinbergen Institute, 2002)
Estimates of the effect of education on GDP (the social return) have been hard to reconcile with micro evidence on the private return to schooling. We present a simple explanation combining two ideas: imperfect substitution and endogenous skill-biased technological progress and use cross-country panel data on inequality and GDP to test these ideas. A one-year increase in the level of education reduces the private return by 2 percentage points, consistent with Katz-Murphy's (1992) elasticity of substitution. We find no evidence for reversal of this initial effect as in Acemoglu (2002). In the short run, the social return equals the private return.
Keywords: E20; J24; O10; O15; 330; education; inequality; growth; Bildungsökonomik; Wachstumstheorie; Einkommensverteilung; Bildungsertrag; Lohnstruktur; Humankapital; Faktorsubstitution; Schätzung; Theorie; Welt